(untitled) (Medical Forum Monthly, 2023)
Objective: To determine relationship in-between uptake of FDG and NLR (neutrophil-lymphocyte ratio), which is an indicator of systemic inflammation, both prior to treatment as well as after treatment in various solid and hematological cancers. Study Design: comparative cross sectional observational study Place and Duration of Study: This study was conducted at the at Clifton and North campus of Dr Ziauddin University for 1 year (March 2022 to February 2023. Materials and Methods: This study using non-probability purposeful sampling was done. Cancer patients >18 years of age, having definitive diagnosis of malignancy, consenting for pre-therapeutic FDG-PET/CT imaging and differential blood analysis done were included. SPSS version 23.0 was used. For quantitative variables mean and IQR were reported while for qualitative variables were recorded as frequency and percentages. Stratification was carried our before and after treatment by applying chi-square test keeping p-value <0.05 as statistically significant. Results: From 237 patients with mean age 52.47 ± 15.5 years, 147 (62%) females and 90 (38%) males. Diagnosis of lymphoma was reported in 72 (30.4%) of patients. A significant difference was observed in the pre and post treatment values of SUV max (p-0.01), NLR (p-0.04), C-reactive protein (p-0.03) and ESR (p-0.04). Majority of patients included were females (62 %) with the highest diagnosis being of lymphoma (30.4%) while least common diagnosis was of sarcoma and melanoma in 0.84 % of patients each. Conclusion: Both SUV max uptake of PET/CT imaging and NLR showed significant decrease after treatment of cancer patients.